Багаторівневе впровадження політики інформаційної безпеки у ВНЗ - Жежнич, Павло; Бурак, Теодор (Видавництво Львівської політехніки, 2018)
The paper considers peculiarities of information security policy implementation at HEI. The proposed approach takes into account variety of HEI’s activities and its complex organization structure. The policy should be implemented at several levels either from defining general aims of information security to information asset protection needs or vice versa.
Keywords: information policy; HEI; information system; information security; data protection